Website Quality Assurance through Combined Automated and Manual Auditing - Balarin, Dan (2025)
This thesis addresses the challenge of comprehensive website quality assurance by developing an integrated approach that combines automated and manual auditing techniques. Current website evaluation solutions typically focus on isolated aspects of quality, such as accessibility, performance, or security, creating a fragmented auditing process that may overlook critical interdependencies. The thesis identifies key metrics across multiple quality dimensions and implements a unified platform that enables complex assessment without requiring access to source code or internal systems. The developed application automates the evaluation of technically measurable aspects while providing guidance for elements requiring human judgment, allowing for comparative analysis across multiple audit iterations. The research contributes both a practical application and a deeper understanding of how different quality categories collectively impact user experience and business outcomes, advancing the field of website quality assurance for practitioners seeking to create and maintain high-quality web experiences.